Salahuddin Wahid and the Defence of Minority Rights in Contemporary Indonesia - Asfa Widiyanto (Al-Jami'ah Research Centre, 2014)
This paper discussed the role and authority of Salahuddin Wahid, a prominent muslim scholar, who actively promotes the minority rights in modern-day Indonesia. His credentials as a traditional ulama coming from the tradition of a pesantren allow him to become an authority in Islamic matters. Salahuddin’s recognition as muslim scholar is in some ways observable from his responses to religious questions posed by the people, either directly or through social media. A general observation of Salahuddin’s Twitter account will allows us to realize that he also represent an authority in “cyber-Islam”. He felt the growing importance of social media, as well as the necessity to promote inclusive religiosity and the respect of minority rights through social media, accordingly he actively promotes his ideas through social media most particularly Twitter. Some issues have been discussed to overview Salahuddin’s ideas to best promote minority rights. His activism can be felt most notably in the following issues: ethnic minorities, women’s rights, religious minorities, diminishing the violence against the Ahmadiyya, and the marriage of religious minorities.[Paper ini membincangkan peran dan otoritas Salahuddin Wahid, seorang intelektual muslim terkemuka yang aktif mempromosikan hak-hak kelompok minoritas di Indonesia. Karisma yang dimilikinya sebagai seorang ulama yang berasal dari kalangan pesantren tradisional memberinya sebuah otoritas dalam berbagai aspek ajaran Islam. Keulamaannya dalam batas tertentu dapat ditelusuri lewat respons yang diberikan atas pertanyaan masyarakat yang diajukan kepadanya, baik secara langsung maupun lewat sosial media. Pengamatan umum terhadap akun Twitter Salahuddin Wahid sekaligus menunjukkan otoritasnya di dunia maya. Dia sadar betul pentingnya sosial media sebagaimana pentingnya mempromosikan keberagamaan inklusif dan penghormatan terhadap hak-hak kelompok minoritas. Karenanya, dia aktif menyuarakan pendapatnya lewat sosial media, khususnya Twitter. Beberapa masalah didiskusikan dalam tulisan ini untuk melihat secara umum pemikiran Salahuddin Wahid terkait dengan hak-hak kelompok minoritas: minoritas etnis, minoritas agama, hak-hak perempuan, kekerasan terhadap Ahmadiyyah, dan pernikahan antar agama.]